'We are creating conditions for young people that are un‐survivable': An interview with Sanah Ahsan. Issue 1 (27th April 2022) - Ahsan, Sanah; Williams, Emma
Abstract: Sanah Ahsan is an award‐winning poet and a qualified clinical psychologist. Ahsan has a growing profile in the public conversation about mental health. She is currently building anti‐racism as a core competence into clinical psychology training. Her work has been featured by the BBC, Channel 4, Shakespeare's Globe and Southbank's WoW festival. She presented the 'Dispatches' documentary 'Young, British and Depressed'. She has also fronted campaigns for the charity Childline on 'coming out to religious parents' and the therapeutic practice of poetry. Emma Williams spoke to Sanah Ahsan about matters of race, education, the arts, and how she draws on the interconnection between these areas in her own practice and research on mental health.